Flux‐mediated synthesis and photocatalytic activity of NaNbO3 particles. Issue 1 (5th September 2019) - Hamilton, Adam M.; O'Donnell, Shaun; Zoellner, Brandon; Sullivan, Ian; Maggard, Paul A.
Abstract: Using molten‐salt synthetic techniques, NaNbO3 (Space group Pbcm ; No. 57) was prepared in high purity at a reaction time of 12 hours and a temperature of 900°C. All NaNbO3 products were prepared from stoichiometric ratios of Nb2 O5 and Na2 CO3 together with the addition of a salt flux introduced at a 10:1 molar ratio of salt to NaNbO3, that is, using the Na2 SO4, NaF, NaCl, and NaBr salts. A solid‐state synthesis was performed in the absence of a molten salt to serve as a control. The reaction products were all found to be phase pure through powder X‐ray diffraction, for example, with refined lattice constants of a = 5.512(5) Å, b = 5.567(3) Å, and c = 15.516(8) Å from the Na2 SO4 salt reaction. The products were characterized using UV‐Vis diffuse reflectance spectroscopy to have a bandgap size of 3.5 eV. The particles sizes were analyzed by scanning electron microscopy (SEM) and found to be dependent upon the flux type used, from <1 μm to >10 μm in length, with overall surface areas that could be varied from 0.66 m 2 /g (for NaF) to 1.55 m 2 /g (for NaBr). Cubic‐shaped particle morphologies were observed for the metal halide salts with the set of exposed (100)/(010)/(001) crystal facets, while a truncated octahedral morphology formed in the sodium sulfate salt reaction with predominantly the set of (110)/(101)/(011) crystal facets. The products were found to be photocatalytically active for hydrogen production under UV‐Vis irradiation, with the aid of a 1 wt% Pt surface cocatalyst. The platinized NaNbO3 particles were suspended in an aqueous 20% methanol solution and irradiated by UV‐Vis light ( λ > 230 nm). After 6 hours of irradiation, the average total hydrogen production varied with the particle morphologies and sizes, with 753 µmol for Na2 SO4, 334 µmol for NaF, 290 µmol for NaCl, 81 µmol for NaBr, and 249 µmol for the solid‐state synthesized NaNbO3 . These trends show a clear relationship to particle sizes, with smaller particles showing higher photocatalytic activity in the order of NaF > NaCl > NaBr. Furthermore, the particle morphologies obtained from the Na2 SO4 flux showed even higher photocatalytic activity, though having a relatively similar overall surface area, owing to the higher activity of the (110) crystal facets. The apparent quantum yield (100 mW/cm 2, λ = 230 to 350 nm, pH = 7) was measured to be 3.7% for NaNbO3 prepared using the NaF flux, but this was doubled to 6.8% when prepared using the Na2 SO4 flux. Thus, these results demonstrate the powerful utility of flux synthetic techniques to control particle sizes and to expose higher‐activity crystal facets to boost their photocatalytic activities for molecular hydrogen production. Abstract : A salt flux method is used to control particle morphologies and sizes of NaNbO3 in order to increase its photocatalytic rates for hydrogen production.